2010
DOI: 10.1021/je1004609
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Niobium Oxides

Abstract: Thermodynamic properties of three oxides of niobium have been measured using solid state electrochemical cells incorporating yttria-doped thoria (YDT) as the electrolyte in the temperature range T = (1000 to 1300) K. The standard Gibbs energies of formation of NbO, NbO2, and NbO2.422 from the elements can be expressed as: △ f G NbO o ± 547 / J · mol − 1 = − 414 986 + 86 .861 ( T / normalK ) △ f G NbO 2 o ± 548 / J · mol − 1 = − 779 864 + 164 .438 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 44 publications
(177 reference statements)
1
46
0
Order By: Relevance
“…As in the first scenario, the temperature was 150 °C. In the absence of any thermodynamic data for niobium minerals, the solid phase considered in the modeling was Nb 2 O 5 , the behaviour of which was modeled using the thermodynamic data of Jacob et al (2010). Thermodynamic data for other minerals precipitated in the reaction were obtained from Holland and Powell (1998) and Robie and Hemingway (1995), and thermodynamic data for the aqueous species not considered in this study were obtained from Johnson et al (1992), Shock et al (1997), and Sverjensky et al (1997).…”
Section: Applications To Natural Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the first scenario, the temperature was 150 °C. In the absence of any thermodynamic data for niobium minerals, the solid phase considered in the modeling was Nb 2 O 5 , the behaviour of which was modeled using the thermodynamic data of Jacob et al (2010). Thermodynamic data for other minerals precipitated in the reaction were obtained from Holland and Powell (1998) and Robie and Hemingway (1995), and thermodynamic data for the aqueous species not considered in this study were obtained from Johnson et al (1992), Shock et al (1997), and Sverjensky et al (1997).…”
Section: Applications To Natural Systemsmentioning
confidence: 99%
“…At the lower end of this HF concentration range, niobium hydroxide species are dominant and therefore our results are directly comparable to those ofPieffert et al (2010) and the theoretical estimates ofShock et al (1997). At the higher end of this HF concentration range our results may be compared qualitatively to those ofZaraisky et al (2010).If the thermodynamic data for the species HNbO 3 , equivalent to the species Nb(OH) 5 , of, are used to estimate the amount of HNbO 3 that might be present in a solution in equilibrium with Nb 2 O 5 (solid) (the thermodynamic properties for Nb 2 O 5 (solid) were taken fromJacob et al, 2010) at a temperature of 150 °C and a pH of ~2 (controlled by the addition of HClO 4 ), the amount of HNbO 3 predicted to be present is on the order of ~10 -2 mol/kg. This amount is more than four orders of magnitude higher than the amounts of niobium hydroxide species observed in this study and in the study ofPieffert et al (2010), and shows that the data ofShock et al (1997) cannot be used to evaluate the mobility of niobium.…”
mentioning
confidence: 96%
“…The minimum energy consumption per switching is given by the free energy difference between two phases at the operation temperature. Table 3 lists the volumetric average heat capacity and latent heat for different materials [7], [209]- [211]. One obvious advantage of Mott memories is that the switching energy per bit will scale with the volume of the device and could be therefore drastically decreased to sub-10-nm size.…”
Section: B Switching Energy Of Phase Transitionsmentioning
confidence: 99%
“…Hence, below this oxygen partial pressure CuO will decompose to Cu 2 O. The similar calculations are done to determine oxygen partial pressure required for the decomposition of Cr 2 O 3 [21] and NbO [22] using free energy values. It is found that the equilibrium partial pressure of oxygen (at 1000 1C) for Cr 2 O 3 is 1.75 Â 10 À 22 atm whereas it is 1.04 Â 10 À 25 atm for NbO.…”
Section: Elementmentioning
confidence: 99%